2019
DOI: 10.3390/quat2020016
|View full text |Cite
|
Sign up to set email alerts
|

Speleothems from the Middle East: An Example of Water Limited Environments in the SISAL Database

Abstract: The Middle East (ME) spans the transition between a temperate Mediterranean climate in the Levant to hyper-arid sub-tropical deserts in the southern part of the Arabian Peninsula (AP), with the complex alpine topography in the northeast feeding the Euphrates and Tigris rivers which support life in the Southeastern Fertile Crescent (FC). Climate projections predict severe drying in several parts of the ME in response to global warming, making it important to understand the controls of hydro-climate perturbation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 166 publications
(250 reference statements)
4
27
0
Order By: Relevance
“…The negative shift in So-1 resonates to a decreased heat transport from the cooled Atlantic inland. The mirrored pattern of δ 18 O from the Dim speleothems is in agreement with the Levantine records [117]. Hence, these variations can similarly be linked to hydroclimatological changes, i.e., less precipitation.…”
Section: Regional Patterns In Carbon-and Oxygen Isotope Recordssupporting
confidence: 84%
See 1 more Smart Citation
“…The negative shift in So-1 resonates to a decreased heat transport from the cooled Atlantic inland. The mirrored pattern of δ 18 O from the Dim speleothems is in agreement with the Levantine records [117]. Hence, these variations can similarly be linked to hydroclimatological changes, i.e., less precipitation.…”
Section: Regional Patterns In Carbon-and Oxygen Isotope Recordssupporting
confidence: 84%
“…Whether the δ 18 O spel -elevation gradient ( Figure 6) prevails over geological timescales, especially under distinct climate settings such as the LGM, can be better explored with an increased number of records, providing a much-improved replication in this specific period. The robustness of these empirical gradients can be further explored extending the study region towards nearby regions [31,117].…”
Section: Assessment Of Spatial Patterns Of Speleothem δ 18 O In the Hmentioning
confidence: 99%
“…This database was compiled to provide a comprehensive understanding of speleothem δ 18 O and δ 13 C records for climate reconstruction and model evaluation (e.g., Comas-Bru et al, 2019). From this database, several papers have already been published that assess data coverage and investigate regional patterns in stalagmite δ 18 O records from specific regions and continents (e.g., Lechleitner et al, 2018;Oster et al, 2019;Braun et al, 2019;Burstyn et al, 2019). To constrain the governing processes influencing speleothem δ 13 C values in the SISAL records we focus on two subsets of the data of the SISAL_v1 database.…”
Section: Introductionmentioning
confidence: 99%
“…CC BY 4.0 License. Burstyn et al, 2019;Deininger et al, 2019;Kaushal et al, 2018;Lechleitner et al, 2018;Oster et al, 2019;Zhang et al, 2019). The potential for using the SISAL database to evaluate climate models was explored using an updated version of the database (SISALv1b; Atsawawaranunt et al, 2019) that contains 455 speleothem records from 211 sites .…”
Section: Open Accessmentioning
confidence: 99%
“…Analyses of the data included in SISALv1 (Braun et al, 2019a;Burstyn et al, 2019;Deininger et al, 2019;Kaushal et al, 2018;Kern et al, 2019;Lechleitner et al, 2018;Oster et al, 2019;Zhang et al, 2019) and SISALv1b (Comas-Bru et al, 2019) revealed a number of errors in specific records that have now been corrected. These revisions include, for example, updates in mineralogies (sample.mineralogy), revised coordinates (site.latitude and/or site.longitude) and addition of missing information that was previously entered as "unknown".…”
Section: Quality Control Of Individual Speleothem Recordsmentioning
confidence: 99%